Resource potential of the medicinal plant Achillea millefolium L. in forest protected areas of the Western and Southern Altai ridges - Mukhtubayeva, S.K.; Kubentayev, S.A.; Izbastina, K.S.; Iskakova, Zh.B.; Bissenova, G.N.; Sarmurzina, Z.S. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
In the article the results of field studies of the medicinal plant Achillea millefolium L. in forest protected areas of the Western and Southern Altai ridges were presented. The total study area covers 4 ranges of the Western Altai (Ivanovsk, Ulbinsk, Ubinsk, Listvyaga) and 3 ranges of the Southern Altai (Narymsk, Kurchumsk and South Altai Tarbagatai). The survey of Achillea millefolium raw material stocks and its ecological state were assessed using generally accepted methods, taking into account intensive harvesting of this plant in the region. In 2 ridges: Ubinsk (Ust-Kamenogorsk SI) and Ivanovsk (Pikhtovsk SI) we have revealed and taken into account that yarrow forms thickets on grass-grassy meadows and along forest edges. Useful properties and uses of Achillea millefolium has a wide range, this is evidenced by their chemical composition: isovalerian, fatty and salicylic acid, asparagine, sterol, phenol, bitter and tannins, alkaloid, flavonoid, glycoside, essential oil, terpenoid, steroid, sesquiterpene derivatives, resins, saponin. The survey of common yarrow showed that raw material should be harvested during flowering. In terms of exploitable reserve, it is noted that it varies in the range of 4.19–7.89 tons. Yarrow raw reserves in the Southern Altai are accounted for in 13 populations, in 4 pilot forest protection institutions: Zyryanovsk State Institution (4 populations); Bolshenarymsk State Institution (2 populations); Katon-Karagai (KK) SNNP (4 populations); Kurchumsk State Institution (3 populations). The exploitable stock in the Southern Altai varies in the range 4.95–118.31 tons. The stocks volume in the following pilot SIs are suitable for commercial harvesting: Bolshenarymsk SI, Katon-Karagay SNNP, Kurchum SI and Zyryanovsk SI.
Батыс жəне Оңтүстік Алтай жоталарының орман қорғау территорияларындағы Аchillea millefolium L. дəрілік өсімдігінің ресурстық əлеуеті
Ресурсный потенциал лекарственного растения Achillea millefolium L. на лесоохранных территориях хребтов Западного и Южного Алтая
Keywords: medicinal plants; Western and Southern Altai; biotopes; stocks of raw materials; stock volume